Expanding Pre-apprenticeship Training Programs as a Model to Improve Recruitment and Retention of Building Construction Tradeswomen. Issue 1 (2nd January 2022) - Wagner, Heidi E.; Kulwiec, Alexia
ABSTRACT: The United States' (U.S.) construction industry is experiencing a labor shortage. Within construction, the most severe worker scarcities are in building trade occupations. In the U.S., though women represent just under half of employed adults, they consist of approximately 3% of trades workers. Thus, increasing women's participation in building trade occupations is one method of addressing workforce needs. A case study methodology examined qualitative data from in-depth interviews highlighting women's entry into the building trades. Findings indicate one key element used to bring more women into trades occupations are trainings referred to as pre-apprenticeship programs. Examination of existing pre-apprenticeship programs within the framework of adult educational theory suggests programs use numerous methods of introducing and training women workers to enter the trades that align with education practices allowing for a changing of perspective and enhanced cultural understanding matching transformative learning methodologies. Conclusions suggest practices honed through decades of work in pre-apprenticeship program procedures could be better supported by unions, contractors, and non-profit organizations to increase the numbers and retention of tradeswomen and, thus, support the worker needs of the overall industry.